Pengembangan Media Pembelajaran Fisika Berbantuan 3D Application Scratch Pada Topik Rotasi Dan Revolusi Untuk Meningkatkan Hasil Belajar Peserta Didik - Ulfa Dina Damayanti; Riki Perdana (Program Studi Pendidikan Fisika Universitas Katolik Widya Mandira, 2024)
Physics requires an innovative learning approach so that students can understand abstract concepts. This research aims to develop physics learning media assisted by 3D Application Scratch on the topic of rotation and revolution to improve students' learning outcomes. Using the 4D development research approach, this research involves four stages: Define, Design, Develop, and Disseminate. In the Define stage, physics learning needs and problems were identified. The Design stage includes learning scenario planning and media design using Scratch. Next, at the Develop stage, the 3D learning media prototype is implemented and then validated. The last stage, Disseminate, is conducted through journal publications. The results of the feasibility test validation score show that Scratch learning media can improve students' learning outcomes, namely for the display aspect of 3.4; the access aspect of 3.0 and the language aspect of 3.75. As obtained from the validation score, Scratch learning media on the topic of rotation and revolution is feasible to use. The results of this study are expected to contribute to the development of innovative learning media to improve the effectiveness of physics learning.